ACUTE TOXICITY STUDIES AND EVALUATION OF ANALGESIC PROPERTY OF TECTONA GRANDIS METHANOLIC SEED EXTRACT IN SWISS ALBINO MICE - JHANSI RANI G; LAKSHMI BHAVANI N (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Tectona grandis which is well known as teak possesses a wide range of applications in Indian and African folklore medicine. All the plant parts are having diverse bioactivities, especially the seeds, having hair growth-promoting activity, anti-inflammatory, and antimicrobial activity. Xanthones, proteins, amino acids, and fatty acids have been isolated from the oil and seeds of T. grandis. Methods: The present study was to explore the antinociceptive properties of methanolic seed extract of T. grandis. Dried seeds of the plant were defatted with non-polar solvents such as petroleum ether and extracted with methanol. Acetic acid-induced writhing test, tail flick test, and tail immersion test were employed for the extract using Swiss albino mice. Results: From the results, it is clear that the methanolic teak seed extract is safe at 1000 mg/kg and having a potent analgesic property (at a dose of 200–250 mg/kg body weight) by inhibiting pain response time. Conclusion: It can be concluded that the methanolic seed extract of T. grandis is analgesic in nature. It is considered as safe and the activity may be due to the presence of various bioactive chemicals such as flavonoids, xanthones, and glycosides.